Endophytic fungi associated with Taxus fuana (West Himalayan Yew) of Pakistan: potential bio-resources for cancer chemopreventive agents. (1st November 2016) - Fatima, Nighat; Kondratyuk, Tamara P.; Park, Eun-Jung; Marler, Laura E.; Jadoon, Muniba; Qazi, Muneer Ahmed; Mehboob Mirza, Hira; Khan, Ibrar; Atiq, Naima; Chang, Leng Chee; Ahmed, Safia; Pezzuto, John M.
Abstract: Context: Endophytic fungi, being a prolific source of bioactive secondary metabolites, are of great interest for natural product discovery. Objective: Isolation and partial characterization of endophytic fungi inhabiting the leaves and woody parts of Taxus fuana Nan Li & R.R. Mill. (Taxaceae) and evaluation of biological activity. Materials and methods: Endophytic fungal isolates were identified by molecular analysis of internal transcribed spacer (ITS) regions of 18S rDNA. Extracts of the endophytic fungi cultured on potato dextrose agar and modified medium were evaluated using cancer chemoprevention bioassays [inhibition of TNF- α -induced NFκB, aromatase and inducible nitric oxide synthase (iNOS); induction of quinone reductase 1 (QR1)] and growth inhibition with MCF-7 cells. Results: Nine of 15 fungal isolates were identified as belonging to Epicoccum, Mucor, Penicillium, Chaetomium, Paraconiothriym, Plectania or Trichoderma . Five of the 15 extracts inhibited NFκB activity (IC50 values ranging between 0.18 and 17 μg/mL) and five inhibited iNOS (IC50 values ranging between 0.32 and 12.9 μg/mL). In the aromatase assay, only two isolates mediated inhibition (IC50 values 12.2 and 10.5 μg/mL). With QR1 induction, three extracts exhibited significant activity (concentrations to double activity values ranging between 0.20 and 5.5 μg/mL), and five extracts inhibited the growth of MCF-7 cells (IC50 values ranging from 0.56 to 17.5 μg/mL). Six active cultures were derived from woody parts of the plant material. Conclusion: The endophytic fungi studied are capable of producing pharmacologically active natural compounds. In particular, isolates derived from the wood of Taxus fuana should be prioritized for the isolation and characterization of bioactive constituents.